A Review of the History and the Current Practice of Aid Evaluation - Ryoh Sasaki (The Evaluation Center at Western Michigan University, 2006)
The study discussed here examined the aid evaluation systems. More than fifty aid agencies were reviewed, under the headings of their major characteristics, criteria, types, volumes, and histories of aid evaluation. Based on preliminary results from this analysis, a meta-evaluation was done to identify best practices (if any) and to propose further study topics.